INVESTIGAÇÃO TEÓRICA DE MATERIAIS COM ESTRUTURA ILMENITA - Ribeiro, Renan Augusto Pontes (2015)
The development of spintronic has motivated the research for new half-metallic magnetic materials due to multifunctionality of these compounds and the spin-based devices fabrication with increased performance as compared to the usual electronic devices. From this perspective, we propose a theoretical investigation of FeBO3 (B = Ti, Zr, Hf, Si, Ge, Sn) ilmenite materials based on Density Functional Theory (DFT) within B3LYP hybrid functional to investigate the B-site cation replacement effect on the structural, elastic, magnetic and electronic properties of ilmenite materials. Calculated structural parameters are in agreement with experimental results and shown that the unit cell volume can be controlled by ionic radius of the B-site metals. The bond distances for FeO6 and BO6 octahedral clarify the Jahn-Teller distortion and Fe-O-B-O-Fe intermetallic connection. The elastic behavior was investigated from bulk modulus and showed that such results were influenced by different material densities. Furthermore, these quantities can be used for analyzing the thermodynamic stability of solids, proving that FeSnO3 and FeHfO3 are unstable due to the negative values for bulk modulus. The B-site radius effect is also evidenced on the magnetic property, where Fe(Ti, Si, Ge)O3 are antiferromagnetic, while Fe(Zr, Hf, Sn)O3 are ferromagnetic. The Mulliken population analysis and charge density maps show the charge corridor formation in the [001] direction due to the intermetallic connection with the B-site metals and electronegativity affecting the stability of ilmenite materials. The Density of States and Band Structure profiles show that antiferromagnetics materials and FeZrO3 are convectional semiconductors, whereas FeHfO3 and FeSnO3 exhibit intrinsic half-metallic behavior, making them promising candidates for spintronic devices.